2020
DOI: 10.1002/jor.24766
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of 23 synovial fluid biomarkers for hip and knee periprosthetic joint infection detection

Abstract: There is interest in novel synovial fluid biomarkers for the detection of periprosthetic joint infection (PJI). Here, we assessed the diagnostic accuracy of 23 simple or sophisticated synovial fluid biomarkers for periprosthetic hip or knee infection detection. One hundred seven subjects were studied, 57 of whom had aseptic failure (AF) and 50 PJI. The following synovial fluid biomarkers were tested using spectrophotometric assays, immunoassays, lateral flow tests, or test strips: leukocyte count, monocyte per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…The arthrocentesis is one of the standard diagnostic procedures. In addition to microbiological cultural bound analyses, the synovial fluid can be examined for cell count or synovial fluid biomarkers [ 7 ] and microbiological multiplex polymerase chain reaction (PCR) approaches. The latter technique allows for rapid pathogen detection, also in combination with the detection of selected molecular antibiotic resistance markers [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The arthrocentesis is one of the standard diagnostic procedures. In addition to microbiological cultural bound analyses, the synovial fluid can be examined for cell count or synovial fluid biomarkers [ 7 ] and microbiological multiplex polymerase chain reaction (PCR) approaches. The latter technique allows for rapid pathogen detection, also in combination with the detection of selected molecular antibiotic resistance markers [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synovial interleukin-6 studies. six studies described the diagnostic accuracy of synovial fluid IL6 in the detection of PJI, using the msis criteria as the standard reference test, [32][33][34][35][36][37] with baseline characteristics of individual studies shown in table iii. The overall sensitivity was 0.86 (95% CI 0.74 to 0.92), specificity was 0.94 (95% ci 0.90 to 0.96), Plr was 13.7 (95% ci 8.6 to 21.6), nlr was 0.15 (95% ci 0.08 to 0.28), and dOr was 89 (95% ci 37 to 214).…”
Section: Resultsmentioning
confidence: 99%
“…First, we searched the databases and removed duplicate records, identifying a total of 169 records. Then, an initial screening of titles and abstracts was performed, resulting in 21 articles that met the precriteria, and 5 articles [ 9 , 10 , 14 16 ] were finally included for quantitative analysis after further evaluation. Figure 1 shows the selection process of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies including a total of 1087 patients (253 patients by PJI) were included in the systematic review to explore the diagnostic accuracy of D-lactate; four studies [ 9 , 10 , 14 , 16 ] were prospective, and one study [ 15 ] was retrospective. Three studies [ 9 , 10 , 14 ] used a D-lactate kit (VL-Diagnostics, Leipzig, Germany) to assess D-lactate, and two studies [ 15 , 16 ] did not give a test method. The average age of the patients included in the study was 66.4–69.5 years, and the proportion of males ranged from 44.6 to 54.7%.…”
Section: Resultsmentioning
confidence: 99%